QUIP: Understanding clients through in-depth interviews (Institute of Development Studies, 2004)
This Practice Note by Imp-Act gives a step-by-step guide to developing and conducting in-depth interviews using the QUIP approach, and analy sing the information and making conclusions based on what you have lea rned.